Experimental investigation of air-conditioning and HDH desalination hybrid system using new packing pad humidifier and strips-finned helical coil. (25th February 2021) - Nada, S.A.; Fouda, A.; Mahmoud, M.A.; Elattar, H.F.
Highlights: An efficient low energy HDH and evaporative AC hybrid system is developed. System productivity and performance increase with increasing air/water flow rates and temperatures and cooling pad thickness. Proposed HDH system has better productivity and performance compared to other systems. Production cost ($/kg) decreases by increasing cooling pad thickness and air and water flow rates and temperatures. Empirical correlations for predicting system productivities and performance parameters. Abstract: A low energy HDH (humidification-dehumidification) and AC (air-conditioning) hybrid system using an efficient design of dehumidifier (strips-finned helical coil) and packing pad material (cellulose paper in bee-hive structure) is proposed. An experimental investigation of the performance of the proposed system is conducted for wide ranges of air and water flow rates and temperatures and packing pad thickness. The results showed that (i) the proposed hybrid system can produce fresh water and remove space cooling load to maintain the required comfort conditions, (ii) the fresh water production rate, cooling load capacity and the system performance increase with increasing air and water flow rates and temperatures and cooling pad thickness, (iii) the proposed HDH system with the new humidification-dehumidification sections has better productivity and performance compared to other systems, (vi) daily production cost of the system increases with increasing inlet air and water flow rates and decreasing cooling pad thickness and air and water temperatures, and (v) production cost per kg of fresh water decreases by increasing cooling pad thickness and air and water flow rates and temperatures. The system performance parameters (fresh water productivity, cooling load capacity, space supply air temperature and coefficient of performance) can reach to 17.42 kg/h, 3.9 kW and 16 °C, and 4.35, respectively. Moreover, the lowest specific cost of fresh water production can be obtained is 0.7 ¢/kgFW, respectively. Finally, empirical correlations of system productivities and performance parameters in terms of operating conditions and system geometric parameters were predicted within acceptable errors.